2010
DOI: 10.3892/or_00000792
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of gemcitabine by Turmeric Force™ in pancreatic cancer cell lines

Abstract: Abstract. Gemcitabine is a first line cancer drug widely used for the treatment of pancreatic cancer. However, its therapeutic efficiency is significantly limited by resistance of pancreatic cancer cells to this and other chemotherapeutic drugs. We have investigated the cytotoxic effect of Turmeric Force™ (TF), a supercritical and hydroethanolic extract of turmeric, alone and in combination with gemcitabine in two pancreatic carcinoma cell lines (BxPC3 and Panc-1). TF is highly cytotoxic to BxPC3 and Panc-1 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…In addition, studies by Kunukkamara et al have demonstrated that curcumin attenuates NF-kB activation, resulting in decreased production of anti-apoptotic factors, including Survivin and cIAP1, as well as pro-angiogenic and metastatic factors, in MiaPaCa-2-derived xenograft tumors (69). Multiple studies have demonstrated synergistic activity between curcumin and Gemcitabine in pancreatic adenocarcinoma cells (40-42). Interestingly, while XIAP is considered to be the most potent regulator of apoptosis in humans, its levels following curcumin treatment remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies by Kunukkamara et al have demonstrated that curcumin attenuates NF-kB activation, resulting in decreased production of anti-apoptotic factors, including Survivin and cIAP1, as well as pro-angiogenic and metastatic factors, in MiaPaCa-2-derived xenograft tumors (69). Multiple studies have demonstrated synergistic activity between curcumin and Gemcitabine in pancreatic adenocarcinoma cells (40-42). Interestingly, while XIAP is considered to be the most potent regulator of apoptosis in humans, its levels following curcumin treatment remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, curcumin induces apoptosis in pancreatic cancer (37) and regulates IAP expression in a variety of other cancer types (38-39). Preclinical studies involving curcumin in pancreatic cancer have shown that curcumin enhances Gemcitabine sensitivity in vitro and in vivo (40-42). Moreover, Phase I and II clinical trials have yielded promising results on the use of curcumin as part of pancreatic cancer therapeutic strategies (43-48).…”
Section: Introductionmentioning
confidence: 99%
“…The intraperitoneal injection of curcumin in corn oil (100 mg/kg/day, each 2 nd day for 18 days) also suppressed the tumor growth of L3.6pL cell xenografted in nude mice [153]. Moreover, curcumin potentiated the anti-proliferative and apoptotic effects induced by gemcitabine, a first-line chemotherapeutic drug, on BxPC-3, Panc-1 and MiaPaCa-2 pancreatic cancer cell lines in vitro [27,154]. A combination of curcumin (1 g/kg, once daily), administered orally plus an intraperitoneal injection of gemcitabine (25 mg/kg, twice weekly) was more effective than single agents at inducing the tumor growth inhibitory and anti-angiogenic effects in a pancreatic tumor model derived from MiaPaCa-2 pancreatic cancer cells orthotopically implanted in nude mice [27,154].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, curcumin potentiated the anti-proliferative and apoptotic effects induced by gemcitabine, a first-line chemotherapeutic drug, on BxPC-3, Panc-1 and MiaPaCa-2 pancreatic cancer cell lines in vitro [27,154]. A combination of curcumin (1 g/kg, once daily), administered orally plus an intraperitoneal injection of gemcitabine (25 mg/kg, twice weekly) was more effective than single agents at inducing the tumor growth inhibitory and anti-angiogenic effects in a pancreatic tumor model derived from MiaPaCa-2 pancreatic cancer cells orthotopically implanted in nude mice [27,154]. The chemosensibilizing effects of curcumin were mediated at least in part via the inhibition of STAT-3 and NF-kB-regulated gene products such as cyclin D1, c-Myc, Bcl-2, Bcl-xL, cellular IAP-1, COX-2, MMPs and VEGF in pancreatic cancer cells (Figures 1 and 2) [27,154].…”
Section: Introductionmentioning
confidence: 99%
“…The formula for manual calculation is rather complicated and involves computing SE(log(D)) when D=Dm (shown in eq. 14, Table 5) but may be obtained using any software that implements this calculation such as Calcusyn or Compusyn (Bijnsdorp et al, 2011;Ikeda et al, 2011;Ramachandran et al, 2010). In practice the threshold value will be the minimal dose where the fraction of dead cells is higher than that of untreated cells.…”
Section: Calculating the Median Dose: The Median Effect Equationmentioning
confidence: 99%